AN APPARENT ABSENCE. AFRICANS AND AFROMESTIZOS IN LATE COLONIAL VALPARAÍSO, 1770-1820. - Contreras Segura, María Teresa (Revista de Historia Social y de las Mentalidades, 2014)
The aim of this paper is to present the systematization of information reviewed about people of African descent residing in late colonial Valparaiso. Population recorded in the Matriz El Salvador church in both 555 baptismal items registered between 1769 and 1824, and 182 marriages performed between 1756 and 1821 in which one or both spouses had African origins. Information showing the presence of men, women, children and adults, slave and free, local and foreign, that are corroborated various mixing processes. Furthermore, data from parish register were compared with three censuses of the time, ie a Matrícula 1777 registration a Padrón 1787 and 1813 Census, showing socio-ethnic diversity of the population of Valparaíso by analyzing the appellatives of “caste” that indicate the ‘taxonomy’ with which priests recognize these people in their parish books, which gave them a place in the colonial social order conditioned by the African ascending and miscegenation.